Nature versus nurture: A case report comparing the clinical and cephalometric pattern in twins (Indian Journal of Case Reports, 2019)
Malocclusion is a manifestation of genetic and environmental interaction on the development of the orofacial region. Orthodontists may be interested in genetics to help understand why a patient has a particular occlusion. Orthodontists usually assume that the genetic factors are of major significance to the development of malocclusion. Studies of twin similarities have lent support to this concept. Twin study is one of the most effective methods available for investigating genetically determined variables of malocclusion. Discordancy is a frequent finding in dizygotic twins. However, discordancy in monozygotic (MZ) twins is a rare finding. Here, we report the case of MZ female twins aged 16 years and a comparison of the clinical and cephalometric pattern was done in both the twins. The present case shows discordancy between MZ female twins in relation to their extraoral and intraoral findings. The purpose of this study of MZ twins is to assess the genetic and environmental components of variation within the cranio-dento-facial complex.